Coping With Metal Toxicity – Cues From Halophytes - Nikalje, Ganesh C.; Suprasanna, Penna (Frontiers in Plant Science, 2018)
Being native flora of saline soil, halophytes are well studied for their salt tolerance and adaptation mechanism at physiological, biochemical, molecular and metabolomic levels. However, these saline habitats are getting contaminated due to various anthropogenic activities like urban waste, agricultural runoff, mining, industrial waste rich is toxic metals and metalloids. These toxic metals also impose different detrimental effects on plants growth and development. Halophytes by virtue of their tolerance to salinity, also show high tolerance to heavy metals. Although applications of halophytes in phytoextraction, rhizofiltration, phytovolatilization, and phytostabilization have been known, information needs to be generated about the mechanism of metal tolerance, detoxification and cross tolerance with other abiotic stresses in halophytes as compared to other plants. In this article, we present an overview of heavy metal tolerance in case of halophytes, the mechanism and cross tolerance with other abiotic stresses.